The Central African Republic : Request for the Disbursement Under the Rapid Credit Facility. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses the Request of Central African Republic for Disbursement Under the Rapid Credit Facility (RCF). Central African Republic is emerging slowly from a dramatic security and political crisis that started in 2013, but daunting challenges remain. Security conditions are improving and the inclusive political dialogue continues. Most of the country is now under government control after the full deployment of international forces. The authorities are implementing economic reforms and have put together an election schedule with a view to end the political transition by mid-December 2015. The IMF staff supports the authorities' request for a third disbursement under the RCF.